The Influence of Current Ratio & Debt To Equity Ratio on Return Of Equity at Bank BTPN for the Period 2013 - 2023 - Fitra Nadira; Elia Putri; Shela Difa Fusfita; Nurwita Nurwita (Scieclouds Publishing, 2025)
This study investigates the impact of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) at Bank BTPN during the period 2013 to 2023. The objective is to understand how these financial metrics affect the bank's profitability. This study uses a quantitative approach, analyzing secondary data sourced from Bank BTPN's annual financial statements. The analysis includes testing classical assumptions (normality, multicollinearity, heteroscedasticity, and autocorrelation) followed by multiple linear regression to explore the relationship between the variables. The findings reveal a stable Current Ratio (CR), fluctuating between 1. 17 and 1. 23, indicating the bank's ability to meet short-term obligations. In contrast, Debt To Equity Ratio (DER) shows a significant decline from 5. 99 in 2013 to 3. 64 in 2023, reflecting a reduced reliance on debt. Although liquidity and capital structure remain healthy, Return Of Equity (ROE) declines from 22% in 2013 to 6% in 2023, indicating challenges in profitability despite good fund management. The results show that although Current Ratio (CR) is positively correlated with Return Of Equity (ROE), its impact remains insignificant. On the other hand, Debt To Equity Ratio (DER) exhibits a significant negative effect on Return Of Equity (ROE), implying that higher reliance on debt negatively impacts profitability. Overall, the study highlights the interrelated nature of these financial ratios and underlines the critical need for banks to optimize their financial structure to improve performance in a competitive sector.